As formas nominais anafóricas no gênero fórum de discussão do orkut - GALVÃO, Alessandro Nobre (2008)
In this work, we propose an analysis of some types of referenciation strategies that contribute for the argumentative orientation in the genre forum of discussion at Orkut. In doing so, we trace a theoretical route in which we discuss concepts as virtual community, genre and referenciation phenomenon. Concerning the first category, we take into account the theoretical postulates of Sociology, Social Learning Theory, and Applied Linguistics in order to propose a concept of virtual community that fits the virtual associations verified in the Orkut website. Concerning the second category, we based our observations, in the genre focused, on the theoretical postulates of Bakhtin (1999; 2003), Rojo (2005), and Rodrigues (2005). These authors define genre under a social and historic perspective. Regarding the last category, we consider authors from Textual Linguistics that discuss the referenciation phenomenon and its theoretical implications. We adopted Kochs (2004; 2005; 2006) taxonomic and analytical propose of the anaphoric strategies with noun heads. These strategies are noun descriptions, anaphoric encapsulations and metadiscoursive labels. The analysis of such process in our corpus was based on both the postulates of referenciation, inscribed in the Textual Linguistics field, and on the considerations of the dialogic nature of genres, inscribed in the Linguistics of Enunciation field.